Theoretical Prerequisites for the Application of Interactive and Active Methods of English Language Instruction in Distance Learning - Saurbayev, Rishat; Dauletmuratova, Mexriban; Satylkhanova, Gulmira; Nazarova, Gaziza; Yerekhanova, Fatima (Journal of Ecohumanism, 2024)
This article examines the theoretical prerequisites for the use of active, and interactive methods of teaching English in the conditions of distance learning. The analysis of literary sources and the semantic understanding of the content of the research topic made it possible to develop a methodological apparatus for distance learning. The research objective of the article: theoretical justification of the use of active and interactive methods of teaching English in the conditions of distance learning. The object of the study is the process of distance teaching of the English language. The subject of the study is the use of active and interactive methods of distance teaching of English. Within the framework of the study, the following hypothesis is put forward if digital means are used in the process of distance teaching as an important condition of a distance learning system. It is necessary to take into account their content components, and the relationship with the taxonomy of learning goals, and learning experience, since this will reflect the activity, and interactivity of teaching English in distance learning.